PERCEPTIONS OF THE PORTUGUESE COMMUNITY SCHOOL LEADERS IN THE UNITED STATES: A MULTIPLE CASE STUDY - António V. Bento (European Scientific Journal, ESJ, 2015)
Many ethnic communities in the United Sates have founded community schools to perpetuate in their new land their cultural “roots”, their own languages and their values. The Portuguese community in the United States is not exception and founded their first school almost one hundred years ago to promote the language and the culture of their ancestors. The purpose of this qualitative study, multiple case work, is to analyze the perceptions of six school community leaders about the context of the Portuguese community schools in the United States namely on the problems they face today, the type of leadership of the schools and the reasons of parents to place their children attending those schools. The narratives of the six leaders interviewed are consistent with common conclusions specifically that the schools face many problems nowadays related with lower enrollments and finances, lack of coordination, poor communication and collaboration among the Portuguese community schools although they benefit from a voluntary, dynamic and democratic type of leadership. These community schools are essential for the Portuguese communities in the United States. They represent the culture, the history and the special “link” to Portugal. For those reasons, these schools should be cared for and recognized by their efforts, leaderships and perpetuation of the national identity and values of our ancestors. It’s extremely important that these community schools be supported and cared for because they provide an important service to the Portuguese communities and to its students